Improving Social Competence for Early Childhood Educators through In House Training - Hariyani, Ade; Yuliantina, Irma (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This study aims to improve the social competence of early childhood education educators at An Nash Islamic Kindergarten through the in-house training (IHT) program. Social competence is one of the four basic competencies that teachers must have, which includes the ability to collaborate, communicate effectively, and involve parents and the community in the learning process. Although online training has previously been conducted, the results have not shown significant improvement. Therefore, IHT is designed to provide training that is more focused and relevant to the needs of educators. The research method used is a qualitative approach with data collection techniques through observation, interviews, and documentation. The results showed that the implementation of IHT at An Nash Islamic Kindergarten successfully improved educators' understanding and social skills. The program involves three stages, namely planning, implementation, and evaluation, which are carried out systematically to ensure the effectiveness of the training. A training needs analysis was conducted to identify gaps and find appropriate solutions. The research shows that although there is progress in educators' social competencies, continuous training is still needed to achieve optimal competencies. IHT proved to be an effective solution to improve educators' social competence in ECD settings, with an emphasis on collaboration and involvement of parents and communities. This study provides recommendations for the implementation of a more structured and sustainable training program to support teachers' professional development in the future.